Jezik(i) - Language(s) and tongue(s) in idioms - Sabine Buchwald (DiSlaw, 2024)
This article focuses on multilingualism concerning the terms language(s) and tongue(s), which use the term jezik(i) in the Slovene language. The two dimensions of meaning are illustrated using quoted phrases from the electronic dictionary of Slovenian phrasemes by Janez Keber (Fran.si) and Slovenian text excerpts from literary works. The advantage of multilingualism and the possibility of expanding competence by searching for equivalents to Slovenian phrases in German and other Slavic languages are emphasized.